MENDIDIK KONSUMEN MELALUI CORPORATE SOCIAL RESPONSEBILITY - Bayquni, Bayquni (Universitas Prof. Dr. Moestopo (Beragama), 2013)
Marketing through advertising has always longed for, that the appeal of its products obtain a much affecting the purchase and continuously. So that advertisers and marketers too, vigorously conduct educational activities to the public through its products. But we realize it or not, it turns out that consumers are learning to do, very much. And they are not aware of the impact of the product is consumed. Therefore, through this paper, the authors will provide an overview kegitana importance of CSR as a form of continuity of pengedukasian ads.